Growth inhibitor for forming pellicle protective thin film, method for forming pellicle protective thin film using the same, and mask manufactured therefrom

JP7637759B2Active Publication Date: 2025-02-28SOULBRAIN CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023500088
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-08
Filing Date
2021-07-06
Publication Date
2025-02-28
Estimated Expiration
2041-07-06

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、ペリクルの透過度を低下させずに腐食や劣化を防ぎ、これを採用したマスクの寿命を大きく改善させることができるペリクル保護薄膜形成用成長抑制剤、これを用いたペリクル保護薄膜形成方法、及びこれから製造されたマスクを提供するという効果がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637759000010
    Figure 0007637759000010
  • Figure 0007637759000011
    Figure 0007637759000011
  • Figure 0007637759000012
    Figure 0007637759000012
Patent Text Reader

Abstract

The present invention relates to a growth inhibitor for forming a pellicle protective thin film, a method for forming a pellicle protective thin film using the same, and a mask manufactured using the same, and more specifically, to a compound represented by the following chemical formula 1: [Chemical formula 1]AnBmXoYiZj (wherein A is carbon or silicon; B is hydrogen or alkyl having 1 to 3 carbon atoms; X is at least one of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I); Y and Z are independently at least one selected from the group consisting of oxygen, nitrogen, sulfur, and fluorine, and are not identical to each other; n is an integer of 1 to 15; o is an integer of 1 or greater; m is a range of 0 to 2n+1; and i and j are integers of 0 to 3.) The present invention provides a growth inhibitor for forming a pellicle protective thin film, a method for forming a pellicle protective thin film using the same, and a mask manufactured using the same. The present invention has the effect of providing a growth inhibitor for forming a pellicle protective thin film, which can prevent corrosion and deterioration without reducing the transmittance of the pellicle, and significantly improve the lifespan of a mask employing the same, a method for forming a pellicle protective thin film using the same, and a mask manufactured using the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a growth inhibitor for forming a pellicle protective thin film, a method for forming a pellicle protective thin film using the same, and a mask manufactured from the same, and more specifically, to a growth inhibitor for forming a pellicle protective thin film that can prevent corrosion and deterioration without reducing the transmittance of the pellicle and significantly improve the life of a mask that employs the same, a method for forming a pellicle protective thin film using the same, and a mask manufactured from the same. [Background technology]

[0002] As memory and non-memory semiconductor devices become more and more integrated and their structures become more complex, step coverage becomes increasingly important when depositing various thin films onto a substrate.

[0003] The semiconductor thin film is made of metal nitride, metal oxide, metal silicide, etc. The metal nitride thin film includes titanium nitride (TiN), tantalum nitride (TaN), zirconium nitride (ZrN), etc., and is generally used as a diffusion barrier between a doped silicon layer of a semiconductor and aluminum (Al), copper (Cu), etc., which are used as interlayer wiring materials. However, when a tungsten (W) thin film is deposited on a substrate, it is used as an adhesion layer.

[0004] In order for the thin film deposited on the substrate to have excellent and uniform physical properties, it is essential that the thin film formed has high step coverage. Therefore, the ALD (atomic layer deposition) process, which utilizes surface reactions, is used rather than the CVD (chemical vapor deposition) process, which mainly utilizes gas phase reactions, but there are still problems in achieving 100% step coverage.

[0005] In addition, in the case of titanium tetrachloride (TiCl4) used to deposit titanium nitride (TiN), a representative example of the metal nitrides, process by-products such as chlorides remain in the thin film produced, which induces corrosion of metals such as aluminum, and also leads to deterioration of film quality due to the problem of the generation of non-volatile by-products.

[0006] Therefore, it is necessary to develop a method for forming a thin film that is capable of forming a complex thin film structure and does not corrode the interlayer wiring material, and a semiconductor substrate manufactured using the method.

[0007] Furthermore, in semiconductor devices, liquid crystal display panels, and the like, photolithography is used for patterning wafers or liquid crystal substrates.

[0008] In the photolithography, a mask is used as a patterning original, and the pattern on the mask is transferred to a wafer or a liquid crystal substrate. However, if impurities such as dust or foreign matter adhere to the mask, the impurities will absorb or reflect light, damaging the transferred pattern, resulting in a decrease in the yield and performance of semiconductor devices, liquid crystal display panels, etc.

[0009] Therefore, a method of coating the surface of the mask with a pellicle has been proposed to prevent impurities from adhering to the surface of the mask, but when the conventional pellicle is coated on the surface of the mask, there are problems such as poor transparency and deterioration of the pellicle itself. Therefore, there is an urgent need to develop a pellicle that can significantly improve the lifespan of the mask without reducing transmittance or causing corrosion or deterioration. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Korean Patent Publication No. 2006-0037241 Summary of the Invention [Problem to be solved by the invention]

[0011] In order to solve the problems of the prior art as described above, the present invention aims to provide a growth inhibitor for forming a pellicle protective thin film that can prevent corrosion and deterioration without reducing the transmittance of the pellicle and significantly improve the life of a mask using the same, a method for forming a pellicle protective thin film using the same, and a mask manufactured using the same.

[0012] The above and other objects of the present invention can all be achieved by the present invention as described below. [Means for solving the problem]

[0013] In order to achieve the above object, the present invention provides a compound represented by the following formula 1:

[0014] [Chemical formula 1] AnBmXoYiZj

[0015] (A is carbon or silicon, B is hydrogen or an alkyl having 1 to 3 carbon atoms, X is one or more of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), Y and Z are independently one or more selected from the group consisting of oxygen, nitrogen, sulfur and fluorine, and are not identical to each other, n is an integer of 1 to 15, o is an integer of 1 or more, m is 0 to 2n+1, and i and j are integers of 0 to 3).

[0016] The growth inhibitor for forming a pellicle protective thin film of the present invention may also be provided as a pellicle protective film quality improver.

[0017] The present invention also provides a method for forming a pellicle protective thin film, comprising the steps of injecting the growth inhibitor for forming the pellicle protective thin film into an ALD chamber and adsorbing the growth inhibitor on a surface of a loaded pellicle.

[0018] The present invention also provides a mask manufactured by the above-mentioned method for forming a pellicle protective thin film.

[0019] The present invention may also provide a mask comprising a mask and a pellicle covering a surface of the mask, the pellicle being made of CNTs (carbon nanotubes), fullerenes or a mixture thereof, and the surface of the pellicle being coated with a protective thin film. Effect of the Invention

[0020] According to the present invention, there are provided a growth inhibitor for forming a pellicle protective thin film, which can prevent corrosion and deterioration without reducing the transmittance of the pellicle and greatly improve the life of a mask employing the same, a method for forming a pellicle protective thin film using the same, and a mask manufactured from the same. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a process diagram for explaining a conventional ALD process. [Diagram 2] FIG. 1 is a process diagram illustrating an ALD process according to one embodiment of the present invention. [Diagram 3] 1 is a SIMS (Secondary Ion Mass Spectrometry) analysis graph (1) showing the reduction rate of Cl element and the like depending on the deposition temperature for Example 1 (SP-TiCl4) of the present invention and Comparative Example 1 (TiCl4). [Figure 4] 1 is a SIMS (Secondary Ion Mass Spectrometry) analysis graph (2) showing the reduction rate of Cl element and the like depending on the deposition temperature for Example 1 (SP-TiCl4) of the present invention and Comparative Example 1 (TiCl4). [Diagram 5]4 is a TEM (Transmission Electron Microscope) photograph of a cross section near the top and near the bottom of a TIN thin film formed in Example 1 (SP-TiCl4) of the present invention and Comparative Example 1 (TiCl4). [Figure 6] 6 is an explanatory diagram of the cross-sectional positions of the top and bottom of FIG. 5. FIG. [Figure 7] 1 is a SIMS analysis graph of SiN thin films produced in Example 5 and Comparative Example 4. [Figure 8] This is an XRD (X-ray diffraction) analysis graph for a sample in which no growth inhibitor for forming a pellicle protective thin film was added (Ref TiN), as in Comparative Example 1, a sample in which a growth inhibitor for forming a pellicle protective thin film was added at a rate of 0.1 g / min in Example 4 (tert-BuI (0.1 g / min)), and a sample in which a growth inhibitor for forming a pellicle protective thin film was added at a rate of 0.1 g / min in Example 4 (tert-BuI (0.1 g / min)). [Figure 9] 1 is a SIMS analysis graph showing the reduction rate of F (fluorine), C (carbon), and other elements depending on the deposition time (Sputter Time) for Example 6 (SP-NbF5) of the present invention and Comparative Example 5 (NbF5). Here, the graph on the right is a graph in which the growth inhibitor for forming a pellicle protective thin film of the present invention is applied, and the graph on the left is a graph for Comparative Example 5, which corresponds to a reference (reference standard) in which the growth inhibitor for forming a pellicle protective thin film is not used. [Figure 10] 1 shows SEM images of the surfaces of a pellicle film coated with the protective thin film produced in Examples 9 to 11 and a reference pellicle film (CNT) after H2 plasma treatment. [Figure 11]This is a graph showing the ID / IG values ​​recorded according to the type of pellicle (film) measured by a Raman spectrometer under measurement conditions of an incident laser wavelength of 531 nm and an excitation laser power of 0.3 mW for pellicles (films) coated with the protective thin films produced in Examples 7 to 9 and Comparative Examples 6 to 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The growth inhibitor for forming a pellicle protective thin film according to the present invention, the method for forming a pellicle protective thin film using the same, and the mask produced from the same will be described in detail below.

[0023] The present inventors have confirmed that when a halogen-substituted compound having a predetermined structure is first adsorbed as a thin film growth inhibitor on the surface of a substrate loaded inside an ALD chamber before adsorbing a thin film precursor compound, the growth rate of the thin film formed after deposition is significantly reduced, the step coverage is significantly improved, and the amount of halide remaining as a process by-product is significantly reduced. In addition, when a thin film precursor compound is first adsorbed on the surface of a substrate loaded inside an ALD chamber and then a halogen-substituted compound having a predetermined structure is adsorbed as a thin film growth inhibitor, it behaves as a film quality improver contrary to expectations, the growth rate of the thin film formed is increased, the amount of halide remaining as a process by-product is significantly reduced, and the density, resistivity, etc. of the thin film are significantly improved. In addition, it has been confirmed that when the thin film precursor compound is applied to the formation of a pellicle protective thin film, corrosion and deterioration are prevented without reducing the transmittance of the pellicle, and the life of the mask using this compound is improved. Based on these results, the present invention has been completed by further research.

[0024] The growth inhibitor for forming a pellicle protective thin film of the present invention is represented by the following chemical formula 1

[0025] [Chemical formula 1] AnBmXoYiZj

[0026] (wherein A is carbon or silicon, B is hydrogen or an alkyl having 1 to 3 carbon atoms, X is at least one of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), Y and Z are independently at least one selected from the group consisting of oxygen, nitrogen, sulfur and fluorine (F; fluorine), and are not identical to each other, n is an integer of 1 to 15, o is an integer of 1 or more, m is 0 to 2n+1, and i and j are integers of 0 to 3), and in this case, there is an effect of preventing corrosion and deterioration without reducing the transmittance of the pellicle, and greatly improving the life of the mask using this.

[0027] The pellicles described herein include those commonly referred to in the art to which the present invention pertains, and preferably include pellicle membranes for extreme ultraviolet (EUV) lithography.

[0028] The B is preferably hydrogen or methyl, and the n is preferably an integer of 2 to 15, more preferably an integer of 2 to 10, even more preferably an integer of 2 to 6, and even more preferably an integer of 4 to 6. Within this range, the effect of removing process by-products is high and the step coverage is excellent.

[0029] In the above Chemical Formula 1, the o is preferably an integer of 1 to 5, more preferably an integer of 1 to 3, and even more preferably 1 or 2. Within this range, there is an advantage that the deposition rate is highly reduced and step coverage is further improved.

[0030] The above m is preferably 1 to 2n+1, and more preferably 3 to 2n+1. Within this range, the effect of removing process by-products is high, and step coverage is excellent.

[0031] The Y and Z are preferable examples, and are independently one or more selected from the group consisting of oxygen, nitrogen, and fluorine (F), and are not the same as each other.

[0032] In a preferred embodiment, both of i and j are not 0, and in a specific embodiment, both of i and j are integers of 1 to 3.

[0033] The compound represented by Chemical Formula 1 is preferably a branched, cyclic or aromatic compound, and specific examples thereof include tert-butyl bromide, 1-methyl-1-bromocyclohexane, 1-iodopropane, 1-iodobutane, 1-iodo-2-methylpropane, 1-iodo-1-isopropylcyclohexane, 1-iodo-4-nitrobenzene, 1-iodo-4-methoxybenzene, 1-iodo-2-methylpentane, 1-iodo-4-trifluoromethylbenzene, tert-butyl iodide ... iodide, and one or more selected from the group consisting of 1-methyl-1-iodocyclohexane, 1-bromo-4-chlorobenzene, 1-bromopropane, 1-bromobutane, 1-bromopentane, 1-bromohexane, 1-bromo-2-methylpropane, 1-bromooctane, 1-bromonaphthalene, 1-bromo-4-iodobenzene, and 1-bromo-4-nitrobenzene, in which case the effect of removing process by-products is high, and the effect of improving step coverage and film quality is excellent.

[0034] The compound represented by Chemical Formula 1 is preferably used in an atomic layer deposition (ALD) process, and in this case, it has the advantages of effectively protecting the surface of a pellicle as a growth inhibitor without inhibiting the adsorption of a precursor compound of a protective thin film, and effectively removing process by-products.

[0035] The compound represented by the formula 1 is preferably liquid at room temperature (22°C) and has a density of 0.8 to 2.5 g / cm 3 or 0.8~1.5g / cm 3 The vapor pressure (20°C) may be 0.1 to 300 mmHg or 1 to 300 mmHg, and the solubility in water (25°C) may be 200 mg / L or less. Within this range, there are effects of excellent step coverage, uniformity of the thin film thickness, and improvement of film quality.

[0036] More preferably, the compound represented by Chemical Formula 1 has a density of 0.85 to 2.0 g / cm 3 or 0.85~1.3g / cm 3 The vapor pressure (20°C) is 1 to 260 mmHg, and the solubility in water (25°C) is 160 mg / L or less. Within these ranges, the effect of excellent step coverage, uniformity of the thin film thickness, and improvement of film quality is achieved.

[0037] The method for forming a pellicle thin film of the present invention comprises reacting a compound represented by the following chemical formula 1

[0038] [Chemical formula 1] AnBmXoYiZj

[0039] (wherein A is carbon or silicon, B is hydrogen or an alkyl having 1 to 3 carbon atoms, X is at least one of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), and Y and Z are independently at least one selected from the group consisting of oxygen, nitrogen, sulfur and fluorine (fluorine), and are not identical to each other, n is an integer of 1 to 15, o is an integer of 1 or more, m is 0 to 2n+1, and i and j are integers of 0 to 3) into an ALD chamber and adsorbed onto the surface of the loaded pellicle. In this case, corrosion and deterioration are prevented without reducing the transmittance of the pellicle, and the life of a mask using the same is significantly improved.

[0040] In the step of adsorbing the growth inhibitor for forming the pellicle protective thin film onto the surface of the pellicle, the feeding time of the growth inhibitor for forming the pellicle protective thin film onto the surface of the pellicle is preferably 1 to 10 seconds per cycle, more preferably 1 to 5 seconds, even more preferably 2 to 5 seconds, and even more preferably 2 to 4 seconds, and within this range, there are advantages in that the thin film growth rate is low, and step coverage and cost-effectiveness are excellent.

[0041] In this description, the feeding time of the growth inhibitor for forming a pellicle protective thin film is based on a chamber volume of 15 to 20 L and a flow rate of 0.5 to 5 mg / s, and more specifically, on a chamber volume of 18 L and a flow rate of 1 to 2 mg / s.

[0042] In a preferred embodiment, the method for forming the pellicle protective thin film may include the steps of: i) vaporizing a growth inhibitor for forming the pellicle protective thin film and adsorbing it on the surface of the pellicle loaded in the ALD chamber; ii) performing a first purging of the inside of the ALD chamber with a purge gas; iii) vaporizing a precursor compound of the pellicle protective thin film and adsorbing it on the surface of the pellicle loaded in the ALD chamber; iv) performing a second purging of the inside of the ALD chamber with a purge gas; v) supplying a reaction gas into the ALD chamber; and vi) performing a third purging of the inside of the ALD chamber with a purge gas. In this case, there are advantages in that the growth rate of the protective thin film is appropriately reduced, and even if the deposition temperature is high during the formation of the protective thin film, the generated process by-products are effectively removed, reducing the resistivity of the protective thin film and significantly improving step coverage.

[0043] In yet another preferred embodiment, the method for forming a pellicle protective thin film includes the steps of: i) vaporizing a protective thin film precursor compound and adsorbing it on the surface of a pellicle loaded in an ALD chamber; ii) primarily purging the inside of the ALD chamber with a purge gas; iii) vaporizing a growth inhibitor for forming the pellicle protective thin film and adsorbing it on the surface of the pellicle loaded in the ALD chamber; iv) secondary purging the inside of the ALD chamber with a purge gas; v) supplying a reaction gas into the ALD chamber; and vi) tertiary purging the inside of the ALD chamber with a purge gas. In this case, the thin film growth rate is increased, and even if the deposition temperature is high during thin film formation, the generated process by-products are effectively removed, thereby reducing the resistivity of the thin film and significantly improving the density and crystallinity of the thin film.

[0044] The growth inhibitor and protective film precursor compound for forming the pellicle protective film can be delivered into the ALD chamber preferably by a VFC (Vapor Flow Control) method, a DLI (Direct Liquid Injection) method, or an LDS (liquid delivery system) method, and more preferably by an LDS method.

[0045] The ratio of the amount (mg / cycle) of the growth inhibitor for forming the pellicle protective thin film to the precursor compound of the protective thin film input into the ALD chamber can be preferably 1:1.5 to 1:20, more preferably 1:2 to 1:15, even more preferably 1:2 to 1:12, and even more preferably 1:2.5 to 1:10. Within this range, the reduction rate of the thin film growth rate per cycle (GPC) is high, and the effect of reducing process by-products is large.

[0046] The precursor compound of the pellicle protective thin film is not particularly limited as long as it is a thin film precursor compound typically used in ALD (atomic layer deposition), but is preferably a metal film precursor compound, a metal oxide film precursor compound, a metal nitride film precursor compound, or a silicon nitride film precursor compound, and the metal preferably includes at least one selected from the group consisting of tungsten, cobalt, chromium, aluminum, hafnium, vanadium, niobium, germanium, lanthanum group elements, actinium group elements, gallium, tantalum, zirconium, ruthenium, copper, titanium, nickel, iridium, and molybdenum.

[0047] As an example, the protective thin film precursor compound containing niobium as the metal may be preferably NbF5, in which case there is an advantage that the effect aimed at by the present invention is well exhibited.

[0048] The metal film precursor, metal oxide film precursor, and metal nitride film precursor may each be, for example, at least one selected from the group consisting of metal halides, metal alkoxides, alkyl metal compounds, metal amino compounds, metal carbonyl compounds, and substituted or unsubstituted cyclopentadienyl metal compounds, but are not limited thereto.

[0049] Specific examples of the metal film precursor, metal oxide film precursor, and metal nitride film precursor include tetrachloro titanium, tetrachloro germanium, tetrachloro tin, tris(isopropyl)ethylmethyl amino germanium, tetraethoxyl germanium, tetramethyl tin, tetraethyl tin, bisacetylacetonate tin, trimethyl aluminum, tetrakis(dimethylamino) germanium, bis(n-butylamino) germanium, tetrakis(ethylmethylamino) tin, tetrakis(dimethylamino) tin, and tetrakis(dimethylamino) tin, respectively. The cobalt dicarbonyl cyclopentadienyl cobalt may be at least one selected from the group consisting of, but is not limited to, dicobalt octacarbonyl, CpCo (biscyclopentadienyl cobalt), Co(CO)3(NO) (tricarbonyl nitrosyl), and CpCo(CO)2 (cyclopentadienyl cobalt dicarbonyl cyclopentadienyl).

[0050] Examples of the silicon nitride film precursor include SiH4, SiCl4, SiF4, SiCl2H2, Si2Cl6, TEOS, DIPAS, BTBAS, (NH2)Si(NHMe)3, (NH2)Si(NHEt)3, (NH2)Si(NH nPr)3、(NH2)Si(NH i Pr)3、(NH2)Si(NH n Bu)3、(NH2)Si(NH i Bu)3、(NH2)Si(NH t Bu)3、(NMe2)Si(NHMe)3、(NMe2)Si(NHEt)3、(NMe2)Si(NH n Pr)3、(NMe2)Si(NH i Pr)3、(NMe2)Si(NH n Bu)3、(NMe2)Si(NH i Bu)3、(NMe2)Si(NH t Bu)3、(NEt2)Si(NHMe)3、(NEt2)Si(NHEt)3、(NEt2)Si(NH n Pr)3、(NEt2)Si(NH i Pr)3、(NEt2)Si(NH n Bu)3、(NEt2)Si(NH i Bu)3、(NEt2)Si(NH t Bu)3、(N n Pr2)Si(NHMe)3、(N n Pr2)Si(NHEt)3、(N n Pr2)Si(NH n Pr)3、(N n Pr2)Si(NH i Pr)3、(N n Pr2)Si(NH n Bu)3、(N n Pr2)Si(NH i Bu)3、(N n Pr2)Si(NH t Bu)3、(N i Pr2)Si(NHMe)3、(N i Pr2)Si(NHEt)3、(N i Pr2)Si(NH n Pr)3、(N i Pr2)Si(NH i Pr)3、(N i Pr2)Si(NH n Bu)3、(N i Pr2)Si(NH i Bu)3、(N i Pr2)Si(NH tBu)3、(N n Bu2)Si(NHMe)3、(N n Bu2)Si(NHEt)3、(N n Bu2)Si(NH n Pr)3、(N n Bu2)Si(NH i Pr)3、(N n Bu2)Si(NH n Bu)3、(N n Bu2)Si(NH i Bu)3、(N n Bu2)Si(NH t Bu)3、(N i Bu2)Si(NHMe)3、(N i Bu2)Si(NHEt)3、(N i Bu2)Si(NH n Pr)3、(N i Bu2)Si(NH i Pr)3、(N i Bu2)Si(NH n Bu)3、(N i Bu2)Si(NH i Bu)3、(N i Bu2)Si(NH t Bu)3、(N t Bu2)Si(NHMe)3、(N t Bu2)Si(NHEt)3、(N t Bu2)Si(NH n Pr)3、(N t Bu2)Si(NH i Pr)3、(N t Bu2)Si(NH n Bu)3、(N t Bu2)Si(NH i Bu)3、(N t Bu2)Si(NH t Bu)3、(NH2)2Si(NHMe)2、(NH2)2Si(NHEt)2、(NH2)2Si(NH n Pr)2、(NH2)2Si(NH i Pr)2、(NH2)2Si(NH n Bu)2、(NH2)2Si(NH i Bu)2、(NH2)2Si(NH tBu)2、(NMe2)2Si(NHMe)2、(NMe2)2Si(NHEt)2、(NMe2)2Si(NH n Pr)2、(NMe2)2Si(NH i Pr)2、(NMe2)2Si(NH n Bu)2、(NMe2)2Si(NH i Bu)2、(NMe2)2Si(NH t Bu)2、(NEt2)2Si(NHMe)2、(NEt2)2Si(NHEt)2、(NEt2)2Si(NH n Pr)2、(NEt2)2Si(NH i Pr)2、(NEt2)2Si(NH n Bu)2、(NEt2)2Si(NH i Bu)、(NEt2)2Si(NH t Bu)2、(N n Pr2)2Si(NHMe)2、(N n Pr2)2Si(NHEt)2、(N n Pr2)2Si(NH n Pr)2、(N n Pr2)2Si(NH i Pr)2、(N n Pr2)2Si(NH n Bu)2、(N n Pr2)2Si(NH i Bu)2、(N n Pr2)2Si(NH t Bu)2、(N i Pr2)2Si(NHMe)2、(N i Pr2)2Si(NHEt)2、(N i Pr2)2Si(NH n Pr)2、(N i Pr2)2Si(NH i Pr)2、(N i Pr2)2Si(NH n Bu)2、(N i Pr2)2Si(NH i Bu)2、(N i Pr2)2Si(NH t Bu)2、(N n Bu2)2Si(NHMe)2、(N n Bu2)2Si(NHEt)2、(N nBu2)2Si(NH n Pr)2、(N n Bu2)2Si(NH i Pr)2、(N n Bu2)2Si(NH n Bu)2、(N n Bu2)2Si(NH i Bu)2、(N n Bu2)2Si(NH t Bu)2、(N i Bu2)2Si(NHMe)2、(N i Bu2)2Si(NHEt)2、(N i Bu2)2Si(NH n Pr)、(N i Bu2)2Si(NH i Pr)2、(N i Bu2)2Si(NH n Bu)2、(N i Bu2)2Si(NH i Bu)2、(N i Bu2)2Si(NH t Bu)2、(N t Bu2)2Si(NHMe)2、(N t Bu2)2Si(NHEt)2、(N t Bu2)2Si(NH n Pr)2、(N t Bu2)2Si(NH i Pr)2、(N t Bu2)2Si(NH n Bu)2、(N t Bu2)2Si(NH i Bu)2、(N t Bu2)2Si(NH t Bu)2、Si(HNCH2CH2NH)2、Si(MeNCH2CH2NMe)2、Si(EtNCH2CH2NEt)2、Si( n PrNCH2CH2N n Pr)2、Si( i PrNCH2CH2N i Pr)2、Si( n BuNCH2CH2N n Bu)2、Si( i BuNCH2CH2N i Bu)2、Si( tBuNCH2CH2N t Bu)2、Si(HNCHCHNH)2、Si(MeNCHCHNMe)2、Si(EtNCHCHNEt)2、Si( n PrNCHCHN n Pr)2,Si( i PrNCHCHN i Pr)2,Si( n BuNCHCHN n Bu)2、Si( i BuNCHCHN i Bu)2、Si( t BuNCHCHN t Bu)2, (HNCHCHNH)Si(HNCH2CH2NH), (MeNCHCHNMe)Si(MeNCH2CHNMe), (EtNCHCHNEt)Si(EtNCH2CH2NEt), ( n PrNCHCHN n (Pr)Si( n PrNCH2CH2N n Pr)、( i PrNCHCHN i (Pr)Si( i PrNCH2CH2N i Pr)、( n BuNCHCHN n Bu)Si( n BuNCH2CH2N n Bu)、 , i BuNCHCHN i Bu)Si( i BuNCH2CH2 N i Bu)、( t BuNCHCHN t Bu)Si( t BuNCH2CH2N t (Bu)、(NH t Bu)2Si(HNCH2CH2NH)、(NH t Bu)2Si(MeNCH2CH2NMe)、 (NH t Bu)2Si(EtNCH2CH2NEt)、(NH t )2Si( n PrNCH2CH2N n Pr)、(NH tBu)2Si( i PrNCH2CH2N i Pr)、(NH t Bu)2Si( n BuNCH2CH2N n Bu)、(NH t Bu)2Si( i BuNCH2CH2N i Bu)、(NH t Bu)2Si( t BuNCH2CH2N t Bu)、(NH t Bu)2Si(HNCHCHNH)、(NH t Bu)2Si(MeNCHCHNMe)、(NH t Bu)2Si(EtNCCHCNet)、(NH t Bu)2Si( n PrNCHCHN n Pr)、(NH t Bu)2Si( i PrNCHCHN i Pr)、(NH t Bu)2Si( n BuNCHCHN n Bu)、(NH t Bu)2Si( i BuNCHCHN i Bu)、(NH t Bu)2Si( t BuNCHCHN t ( i PrNCH2CH2N i Pr)Si(NHMe)2、( i PrNCH2CH2N i Pr)Si(NHEt)、( i PrNCH2CH2N i Pr)Si(NH n Pr)2、( i PrNCH2CH2N i Pr)Si(NH i Pr)2、( i PrNCH2CH2N i Pr)Si(NH n Bu)2、( i PrNCH2CH2N i Pr)Si(NH i Bu)2、(i PrNCH2CH2N i Pr)Si(NH t Bu)2, ( i PrNCHCHN i Pr)Si(NHMe)2, ( i PrNCHCHN i Pr)Si(NHEt)2, ( i PrNCHCHN i Pr)Si(NH n Pr)2, ( i PrNCHCHN i Pr)Si(NH i Pr)2, ( i PrNCHCHN i Pr)Si(NH n Bu)2, ( i PrNCHCHN i Pr)Si(NH i Bu)2 and ( i PrNCHCHN i Pr)Si(NH t Bu), but is not limited thereto.

[0051] The above n Pr stands for n-propyl. i Pr stands for iso-propyl n Bu stands for n-butyl, i Bu is isobutyl, t Bu means tert-butyl.

[0052] In one preferred embodiment, the protective thin film precursor compound may be titanium tetrahalide.

[0053] The titanium tetrahalide may be used as a metal precursor of the thin film forming composition. The titanium tetrahalide may be at least one selected from the group consisting of TiF4, TiCl4, TiBr4, and TiI4, and is preferably TiCl4 from the economical viewpoint, but is not limited thereto.

[0054] The titanium tetrahalide has excellent thermal stability and exists in a liquid state without being decomposed at room temperature, and therefore can be used as a precursor for ALD (atomic layer deposition) to deposit a thin film.

[0055] For example, the precursor compound of the protective thin film may be mixed with a non-polar solvent and then poured into the chamber. In this case, there is an advantage that the viscosity and vapor pressure of the precursor compound of the protective thin film can be easily adjusted.

[0056] The non-polar solvent may be at least one selected from the group consisting of alkanes and cycloalkanes. In this case, there is an advantage that the step coverage is improved even if the deposition temperature is increased during thin film formation, while containing an organic solvent having low reactivity and solubility and easy moisture management.

[0057] As a more preferred example, the non-polar solvent may include a C1 to C10 alkane or a C3 to C10 cycloalkane, and is preferably a C3 to C10 cycloalkane, which has the advantages of low reactivity and solubility and easy moisture management.

[0058] In this description, C1, C3 etc. refer to carbon numbers.

[0059] The cycloalkane may be preferably a C3 to C10 monocycloalkane, and among the monocycloalkanes, cyclopentane is preferred in the vapor deposition process because it is liquid at room temperature and has the highest vapor pressure, but is not limited thereto.

[0060] The non-polar solvent, for example, has a solubility in water (25°C) of 200 mg / L or less, preferably 50 to 200 mg / L, and more preferably 135 to 175 mg / L. Within this range, the solvent has the advantages of low reactivity with the protective thin film precursor compound and easy moisture control.

[0061] In this description, the solubility is not particularly limited as long as it is based on a measurement method or standard commonly used in the technical field to which the present invention pertains. As an example, a saturated solution can be measured by HPLC (high-performance liquid chromatography).

[0062] The non-polar solvent may preferably be contained in an amount of 5 to 95% by weight, more preferably 10 to 90% by weight, even more preferably 40 to 90% by weight, and most preferably 70 to 90% by weight, based on the total weight of the precursor compound of the pellicle protective thin film and the non-polar solvent.

[0063] If the content of the non-polar solvent exceeds the upper limit, impurities are induced, increasing the resistance and the number of impurities in the protective thin film. If the content of the organic solvent is less than the lower limit, there is a disadvantage that the effect of improving step coverage by adding the solvent and the effect of reducing impurities such as chlorine (Cl) ions are small.

[0064] In the above-mentioned method for forming a pellicle protective thin film, as one example, the rate of decrease in the thin film growth rate per cycle (Å / cycle), calculated by the following mathematical formula 1, is −5% or less, preferably −10% or less, more preferably −20% or less, even more preferably −30% or less, even more preferably −40% or less, and most preferably −45% or less. Within this range, the step coverage and uniformity of the film thickness are excellent.

[0065] [Formula 1] Decrease rate of thin film growth rate per cycle (%) = [(thin film growth rate per cycle when growth inhibitor for forming pellicle protective thin film is used - thin film growth rate per cycle when growth inhibitor for forming pellicle protective thin film is not used) / thin film growth rate per cycle when growth inhibitor for forming pellicle protective thin film is not used] × 100

[0066] In the method for forming a pellicle protective thin film, the residual halogen intensity (c / s) in the thin film formed after 200 cycles, as measured by SIMS, is preferably 10,000 or less, more preferably 8,000 or less, even more preferably 7,000 or less, and even more preferably 6,000 or less. Within such a range, the effect of preventing corrosion and deterioration is excellent.

[0067] In the present description, the purging rate is preferably 1,000 to 10,000 sccm, more preferably 2,000 to 7,000 sccm, and even more preferably 2,500 to 6,000 sccm. Within this range, the thin film growth rate per cycle is reduced to a preferred range, and process by-products are reduced.

[0068] ALD (atomic layer deposition) is highly advantageous in the fabrication of integrated circuits (ICs) that require high aspect ratios, and has advantages such as excellent conformality, uniformity, and precise thickness control due to its self-limiting thin film growth mechanism.

[0069] The method for forming the pellicle protective thin film may be carried out at a deposition temperature in the range of 50 to 900°C, for example, preferably at a deposition temperature in the range of 300 to 700°C, more preferably at a deposition temperature in the range of 350 to 600°C, even more preferably at a deposition temperature in the range of 400 to 550°C, and even more preferably at a deposition temperature in the range of 400 to 500°C. Within this range, it is effective to grow a thin film of excellent film quality while embodying the characteristics of the ALD process.

[0070] The method for forming a pellicle protective thin film can be carried out, for example, at a deposition pressure in the range of 0.1 to 10 Torr, preferably at a deposition pressure in the range of 0.5 to 5 Torr, and most preferably at a deposition pressure in the range of 1 to 3 Torr. Within this range, it is effective to obtain a thin film of uniform thickness.

[0071] In this description, deposition temperature and deposition pressure may be measured as the temperature and pressure formed in the deposition chamber, or as the temperature and pressure applied to a substrate in the deposition chamber.

[0072] The method for forming a pellicle protective thin film preferably includes a step of raising the temperature in the chamber to a deposition temperature before introducing a growth inhibitor for forming the pellicle protective thin film into the chamber; and / or a step of introducing an inert gas into the chamber to purge the chamber before introducing the growth inhibitor for forming the pellicle protective thin film into the chamber.

[0073] The present invention also provides a thin film manufacturing apparatus capable of implementing the method for manufacturing a pellicle protective thin film, the thin film manufacturing apparatus including an ALD chamber, a first vaporizer for vaporizing a growth inhibitor for forming a pellicle protective thin film, a first transfer means for transferring the vaporized growth inhibitor for forming a pellicle protective thin film into the ALD chamber, a second vaporizer for vaporizing a precursor of a Ti-based protective thin film, and a second transfer means for transferring the vaporized precursor of the Ti-based protective thin film into the ALD chamber. Here, the vaporizer and the transfer means are not particularly limited as long as they are vaporizers and transfer means commonly used in the technical field to which the present invention pertains.

[0074] As a specific example, the method for forming the pellicle protective thin film will be described below. First, a pellicle, on which a thin film may be formed, is placed in a deposition chamber capable of atomic layer deposition.

[0075] The pellicle is, by way of example, positioned on a substrate, which by way of example includes a silicon substrate, a silicon oxide substrate, or the like.

[0076] The substrate may further have a conductive or insulating layer formed thereon.

[0077] In order to deposit a thin film on a substrate positioned in the deposition chamber, the above-mentioned growth inhibitor for forming the pellicle protective thin film and a precursor compound of the pellicle protective thin film, or a mixture of the precursor compound and a non-polar solvent, are prepared.

[0078] Then, the prepared inhibitor for forming the pellicle protective thin film is introduced into a vaporizer, converted into a vapor phase, and transported to the deposition chamber to be adsorbed onto the pellicle surface, and the non-adsorbed inhibitor for forming the pellicle protective thin film is purged.

[0079] Next, the prepared precursor compound of the pellicle protective thin film, or a mixture of the precursor compound and a non-polar solvent, is introduced into a vaporizer, converted into a gas phase, and delivered to a deposition chamber to be adsorbed onto a pellicle, after which unadsorbed composition for forming the pellicle protective thin film is purged.

[0080] In this description, the method of delivering the inhibitor for forming the pellicle protective thin film and the precursor compound of the pellicle protective thin film to the deposition chamber may, for example, be a method of delivering volatilized gas using a mass flow controller (MFC) method (Vapor Flow Control; VFC), or a method of delivering liquid using a liquid mass flow controller (LMFC) method (Liquid Delivery System; LDS), with the LDS method being preferred.

[0081] Here, the carrier gas or dilution gas for moving the inhibitor for forming the pellicle protective thin film and the precursor compound of the pellicle protective thin film onto the pellicle may be one or a mixture of two or more gases selected from argon (Ar), nitrogen (N2), and helium (He), but is not limited thereto.

[0082] In the present description, as the purge gas, for example, an inert gas may be used, and preferably, the above-mentioned carrier gas or dilution gas is used.

[0083] Next, a reaction gas is supplied. The reaction gas is not particularly limited as long as it is a reaction gas commonly used in the technical field to which the present invention belongs, and preferably includes a reducing agent, a nitriding agent, or an oxidizing agent. The reducing agent reacts with the precursor compound of the protective thin film adsorbed on the pellicle to form a metal thin film. In the case of the nitriding agent, a metal nitride thin film is formed, and in the case of the oxidizing agent, a metal oxide thin film is formed.

[0084] Preferably, the reducing agent may be ammonia gas (NH3) or hydrogen gas (H2), the nitriding agent may be nitrogen gas (N2), and the oxidizing agent may be one or more selected from the group consisting of H2O, H2O2, O2, O3, and N2O.

[0085] Next, an inert gas is used to purge the remaining unreacted reactant gas, which removes not only the excess reactant gas but also any by-products that are produced.

[0086] As described above, the steps of adsorbing an inhibitor for forming a pellicle protective thin film onto a pellicle, purging unadsorbed inhibitor for forming a pellicle protective thin film, adsorbing a precursor compound for the pellicle protective thin film onto a substrate, purging unadsorbed precursor compound for the pellicle protective thin film, supplying a reactive gas, and purging residual reactive gas are defined as a unit cycle, and the unit cycle can be repeated to form a thin film of the desired thickness.

[0087] The unit cycle is, for example, 100 to 1000 times, preferably 100 to 500 times, and more preferably 150 to 300 times. Within this range, the desired thin film properties are effectively exhibited.

[0088] Fig. 1 below is a process diagram for explaining a conventional ALD process, and Fig. 2 below is a process diagram for explaining an ALD process according to an embodiment of the present invention. Referring to Fig. 1, when the conventional ALD process is performed, that is, when the growth inhibitor for forming the pellicle protective thin film according to the present invention is not first adsorbed to protect the pellicle surface before adsorbing the precursor compound (e.g., TiCl4) of the pellicle protective thin film, process by-products such as HCl remain in the protective thin film (e.g., TiN) formed by reaction with the reactive gas (e.g., NH3), which reduces the performance of the substrate due to corrosion and deterioration. However, as shown in Figure 2, when the growth inhibitor (TSI) for forming the pellicle protective thin film according to the present invention is adsorbed before the protective thin film precursor compound (e.g., TiCl4) is adsorbed to protect the pellicle surface (Surface Protection; SP), process by-products such as HCl generated by reaction with the reactive gas (e.g., NH3) when forming the protective thin film (e.g., TiN) are removed together with the growth inhibitor for forming the pellicle protective thin film, thereby preventing corrosion and deterioration of the pellicle and further improving the step coverage and uniformity of the thin film thickness by appropriately lowering the thin film growth rate per cycle.

[0089] The mask of the present invention is characterized by being manufactured using the pellicle protective thin film formation method described herein, and in such cases has the advantage of significantly improving the lifespan of the mask employing it by preventing corrosion and deterioration without reducing the transmittance of the pellicle.

[0090] In addition, the mask of the present invention preferably includes a mask and a pellicle covering the surface of the mask, the pellicle being made of CNT, fullerene or a mixture thereof, and the surface of the pellicle being coated with a protective thin film. In such a case, there is an advantage in that corrosion and deterioration are prevented without reducing the transmittance of the pellicle, and the life of the mask employing this is greatly improved.

[0091] The pellicle coated with said protective thin film preferably has a transmittance of 80% or more, more preferably 85% or more.

[0092] The mask described herein may include any configuration not separately described in this specification, as long as it does not conflict with the present invention and is a configuration that is normally included in masks in the technical field to which the present invention pertains.

[0093] The protective thin film thus produced preferably has a thickness of 20 nm or less, a resistivity of 0.1 to 400 μΩ·cm, a halogen content of 10,000 ppm or less, and a step coverage of 90% or more.

[0094] The protective thin film has a thickness of, for example, 5 to 20 nm, preferably 10 to 20 nm, more preferably 15 to 18.5 nm, and further preferably 17 to 18.5 nm. Within this range, the protective thin film has excellent properties.

[0095] The protective thin film has a resistivity of, for example, 0.1 to 400 μΩ·cm, preferably 50 to 400 μΩ·cm, and more preferably 100 to 300 μΩ·cm. Within this range, the protective thin film has excellent properties.

[0096] The protective thin film has a halogen content of more preferably 9,000 ppm or less or 1 to 9,000 ppm, even more preferably 8,500 ppm or less or 100 to 8,500 ppm, and even more preferably 8,200 ppm or less or 1,000 to 8,200 ppm. Within this range, the protective thin film has excellent properties and is effective in reducing corrosion.

[0097] As an example, the protective thin film has a step coverage rate of 80% or more, preferably 90% or more, and more preferably 92% or more. Within this range, even protective thin films with complex structures can be easily deposited on a pellicle, which has the advantage that they can be applied to next-generation semiconductor devices.

[0098] The protective thin film may be, for example, a TiN protective thin film, a TiO2 protective thin film, a NbN protective thin film, a HfO2 protective thin film, or a SiO2 protective thin film.

[0099] Below, preferred embodiments and drawings are presented to aid in understanding the present invention. However, the following embodiments and drawings are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical idea of ​​the present invention. Naturally, such changes and modifications fall within the scope of the appended claims.

[0100] [Example] <Examples 1 to 3> The growth inhibitors for thin film formation and TiCl4 as a thin film precursor compound shown in Table 1 below were prepared. The prepared growth inhibitors for thin film formation were placed in a canister and supplied to a vaporizer heated to 150°C at a flow rate of 0.05g / min using a LMFC (Liquid Mass Flow Controller) at room temperature. The growth inhibitors for thin film formation vaporized to the vapor phase in the vaporizer were introduced into a deposition chamber loaded with a substrate for 1 second. Thereafter, argon gas was supplied at 5000sccm for 2 seconds to perform argon purging. At this time, the pressure in the reaction chamber was controlled to 2.5Torr. Next, the prepared TiCl4 was placed in a separate canister and supplied to a separate vaporizer heated to 150°C at a flow rate of 0.05g / min using a LMFC (Liquid Mass Flow Controller) at room temperature. The TiCl4 vaporized to the vapor phase in the vaporizer was introduced into the deposition chamber for 1 second. After this, argon gas was supplied at 5000 sccm for 2 seconds to perform argon purging. At this time, the pressure in the reaction chamber was controlled to 2.5 Torr. Next, 1000 sccm of ammonia was introduced as a reactive gas into the reaction chamber for 3 seconds, and then argon purging was performed for 3 seconds. At this time, the substrate on which the metal thin film was formed was heated to 460°C. This process was repeated 200 times to form a TiN thin film, which is a self-limiting atomic layer.

[0101] [Table 1]

[0102] <Example 4> The growth inhibitors for thin film formation and TiCl4 as a thin film precursor compound shown in Table 1 were prepared. The prepared growth inhibitors for thin film formation were placed in a canister and supplied to a vaporizer heated to 150°C at a flow rate of 0.05g / min using an LMFC (Liquid Mass Flow Controller) at room temperature. The prepared TiCl4 was placed in a separate canister and supplied to a separate vaporizer heated to 150°C at a flow rate of 0.05g / min using an LMFC (Liquid Mass Flow Controller) at room temperature.

[0103] TiCl4 vaporized into the vapor phase by the vaporizer was introduced into the deposition chamber for 1 second. After that, argon gas was supplied at 5000 sccm for 2 seconds to perform argon purging. At this time, the pressure in the reaction chamber was controlled to 2.5 Torr. Next, the growth inhibitor for thin film formation vaporized into the vapor phase by the vaporizer was introduced into the deposition chamber in which the substrate was loaded for 1 second. After that, argon gas was supplied at 5000 sccm for 2 seconds to perform argon purging. At this time, the pressure in the reaction chamber was controlled to 2.5 Torr. Next, 1000 sccm of ammonia was introduced into the reaction chamber as a reactive gas for 3 seconds, and then argon purging was performed for 3 seconds. At this time, the substrate on which the metal thin film was formed was heated to 440 to 500 ° C. This process was repeated 200 times to form a TiN thin film, which is a self-limiting atomic layer.

[0104] <Example 5> The growth inhibitors for forming a thin film and Si2Cl6 as a thin film precursor compound shown in Table 1 were prepared. The prepared growth inhibitors for forming a thin film were placed in a canister and supplied to a vaporizer heated to 150°C at a flow rate of 0.05g / min using an LMFC (Liquid Mass Flow Controller) at room temperature. The prepared Si2Cl6 was placed in a separate canister and supplied to a separate vaporizer heated to 150°C at a flow rate of 0.05g / min using an LMFC (Liquid Mass Flow Controller) at room temperature.

[0105] The growth inhibitor for thin film formation vaporized into the vapor phase by the vaporizer was introduced into the deposition chamber loaded with the substrate for 1 second, and then argon gas was supplied at 5000 sccm for 2 seconds to perform argon purging. At this time, the pressure in the reaction chamber was controlled to 2.5 Torr. Next, Si2Cl6 vaporized into the vapor phase by the vaporizer was introduced into the deposition chamber for 1 second. After this, argon gas was supplied at 5000 sccm for 2 seconds to perform argon purging. At this time, the pressure in the reaction chamber was controlled to 2.5 Torr. Next, 1000 sccm of ammonia was introduced into the reaction chamber as a reactive gas for 3 seconds, and then a plasma treatment of 200 W was performed. Next, argon purging was performed for 3 seconds. At this time, the substrate on which the metal thin film was formed was heated to 460 ° C. This process was repeated 300 times to form a SiN thin film, which is a self-limiting atomic layer.

[0106] <Example 6> In Example 1, tert-butyl chloride was used as a growth inhibitor for thin film formation, and NbF5 was used as a thin film precursor compound, and the NbN thin film, which is a self-limiting atomic layer, was formed in the same manner as in Example 1, except that it was vaporized by the VFC method instead of the LDS method.

[0107] <Examples 7 to 9> In Example 1, tert-butyl chloride was used as a growth inhibitor for forming the pellicle protective thin film, TiCl4 was used as a precursor compound for the pellicle protective thin film, the substrate was changed to a CNT pellicle, and the thicknesses of the pellicle protective thin film were set to 1 nm, 2 nm, and 3 nm, respectively. A TiN pellicle protective thin film was formed in the same manner as in Example 1, except that.

[0108] <Examples 10 to 12> In Example 9, HfO2, SiO2 and NbN pellicle protective thin films were formed in the same manner as in Example 9, except that CpHf, 1,3,3-tetramethyldisiloxane and NbF5 were used as the pellicle protective thin film precursor compounds, and ozone and ammonia were used as the reactive gases, respectively.

[0109] <Comparative Example 1> A TIN thin film was formed on a substrate in the same manner as in Example 1, except that no growth inhibitor for thin film formation was used and, accordingly, the step of purging the non-adsorbed growth inhibitor for thin film formation was omitted.

[0110] <Comparative Examples 2 and 3> A TiN thin film was formed on a substrate in the same manner as in Example 1, except that pentane or cyclopentane was used instead of the growth inhibitor for thin film formation listed in Table 1 in Example 1.

[0111] <Comparative Example 4> In Example 5, a SiN thin film was formed on a substrate in the same manner as in Example 6, except that no growth inhibitor for thin film formation was used and, accordingly, the step of purging unadsorbed growth inhibitor for thin film formation was omitted.

[0112] <Comparative Example 5> A NbN thin film, which is a self-limiting atomic layer, was formed in the same manner as in Example 6, except that no growth inhibitor for thin film formation was added.

[0113] <Comparative Examples 6 to 8> In Examples 7 to 9, a TiN pellicle protective thin film was formed in the same manner as in Examples 7 to 9, except that no growth inhibitor for forming a pellicle protective thin film was added.

[0114] [Experimental Example] 1) Evaluation of deposition (deposition) As shown in Table 2 below, Example 1, in which tert-butyl bromide was used as a growth inhibitor for thin film formation, was compared with Comparative Example 1, in which tert-butyl bromide was not used. As a result, the deposition rate was 0.19 Å / cycle, which was a decrease of 40% or more compared to Comparative Example 1. It was confirmed that the remaining Examples 2 and 3, and Example 5 also had deposition rates similar to that of Example 1. It was also confirmed that Comparative Examples 2 and 3, in which pentane or cyclopentane was used instead of the growth inhibitor for thin film formation according to the present invention, had the same deposition rate as Comparative Example 1. Here, a decrease in deposition rate means that the CVD deposition characteristics are changed to ALD deposition characteristics, and can be used as an indicator of improvement in step coverage characteristics.

[0115] Also, to confirm whether the same effect is realized in the SiN thin film, Example 5 is compared with Comparative Example 4 with reference to Table 2 below. As a result, it can be seen that the deposition rate of Example 5 is reduced by more than 10%, from 0.29 Å / cycle to 0.32 Å / cycle, compared to Comparative Example 4.

[0116] 7 is a SIMS analysis graph of the SiN thin films manufactured in Example 5 and Comparative Example 4. It was confirmed that Example 5, which corresponds to the graph on the right, has a significantly reduced amount of Cl compared to Comparative Example 4, which corresponds to the graph on the left.

[0117] In addition, referring to Table 2 below, in Example 4 in which the source precursor, i.e., the thin film precursor, was first adsorbed using tert-butyl iodide as a growth inhibitor for thin film formation, and then the growth inhibitor for thin film formation was supplied after argon gas purging, the deposition rate increased by nearly 10% from 0.32 Å / cycle to 0.35 Å / cycle, and when the deposition temperature was increased to 500° C., the deposition rate increased by nearly 16% to 0.37 Å / cycle, compared to Comparative Example 1 in which no growth inhibitor for thin film formation was used.

[0118] In Example 4, the deposition rate is increased compared to Comparative Example 1. However, unlike the conventional technology, an unexpected phenomenon occurs in which impurities are reduced rather than increased when the deposition rate is increased, and it has been confirmed that this provides another significant advantage when linked to the aspect of through-put.

[0119] [Table 2]

[0120] 2) Impurity reduction properties In order to compare the impurity reduction characteristics, i.e., the reduction characteristics of process by-products, of the deposited TiN thin films based on Examples 1 to 5 and Comparative Examples 1 and 2, SIMS analysis was performed, and the results are shown in Table 4 below and Figures 3 and 4. Here, the Cl reduction rate (%) was calculated using the following Equation 2.

[0121] [Formula 2] TIFF0007637759000003.tif14147

[0122] [Table 3]

[0123] *Reference thickness of sample thin film: 10 nm

[0124] As shown in Table 3, in Examples 1 to 5 in which the growth inhibitor for thin film formation according to the present invention was used, the Cl intensity was significantly reduced compared to Comparative Examples 1 and 2 in which the growth inhibitor was not used, and it was confirmed that the impurity reduction characteristics were excellent.

[0125] In addition, by comparing Example 3 with Example 4, it was confirmed that the process method of Example 4 is very advantageous in terms of impurity reduction characteristics.

[0126] In addition, the following Figures 3 and 4 are graphs showing the reduction characteristics of process by-products, i.e., the reduction rate of Cl, according to the deposition temperature in Example 1 and Comparative Example 1. It was confirmed that when the growth inhibitor for thin film formation according to the present invention was used, the intensity of Cl was significantly reduced at all deposition temperatures, especially in the range of 480 to 520°C, compared to when the inhibitor for thin film formation according to the present invention was not used.

[0127] Also, as can be seen from Fig. 9 below, in Example 6, in which the growth inhibitor for thin film formation (tert-butyl chloride) according to the present invention was used and the thin film precursor was changed to the Nb thin film precursor, the strength (c / s) of the contaminants F and C in the film was significantly reduced compared to Comparative Example 5 (Ref NbF5) in which no growth inhibitor for thin film formation was used, and it was confirmed that the impurity reduction characteristics were very excellent. More specifically, in Example 6 (F(c / s)=75,197, C(c / s)=656) in which NbF5 was used as the thin film precursor, the strength of the contaminants F and C in the film was reduced by 35% and 55%, respectively, compared to Comparative Example 5 (F(c / s)=116,925.65, C(c / s)=1,466), which is the reference (reference standard), and it was confirmed again that the Nb thin film according to the present invention has a very excellent impurity reduction characteristic.

[0128] 3) Decrease in thin film growth rate The thin film growth rate of the TiN thin films deposited in Examples 1 to 5 and Comparative Examples 1 and 2 was measured by measuring the thickness using an ellipsometery method, and the thin film growth rate reduction rate was calculated using the following Equation 1 based on the measured thickness. The results are shown in Table 4 below.

[0129] [Formula 1] Decrease rate of thin film growth rate per cycle (%) = [(thin film growth rate per cycle when a growth inhibitor for thin film formation is used - thin film growth rate per cycle when a growth inhibitor for thin film formation is not used) / thin film growth rate per cycle when a growth inhibitor for thin film formation is not used] × 100

[0130] [Table 4]

[0131] As shown in Table 4, it was confirmed that Examples 1 to 3 using the growth inhibitor for thin film formation according to the present invention are superior in terms of the reduction rate of thin film growth rate per cycle, at a level of 10 to 40%, compared to Comparative Example 1, which does not use the growth inhibitor. In addition, when Example 5 is compared to Comparative Example 2, it was confirmed that Example 5 is superior in terms of the reduction rate of thin film growth rate per cycle, at a level of 17%, compared to Comparative Example 2. In addition, when the process method is changed, when Example 4 is compared to Comparative Example 1, the deposition rate of Example 4 is increased compared to Comparative Example 1, but unlike the conventional technology, even if the deposition rate is increased, it has excellent impurity reduction properties, and if it is linked to the aspect of through-put, it can provide another advantage.

[0132] 4) Step coverage characteristics The TiN thin films deposited in Example 1 and Comparative Example 1 were examined for step coverage using a TEM, and the results are shown in Table 5 and FIG.

[0133] [Table 5]

[0134] As shown in Table 5, Example 1 using the growth inhibitor for thin film formation according to the present invention had a significantly higher step coverage rate than Comparative Example 1 not using the growth inhibitor. Also, referring to the TEM photograph in FIG. 5 below, it was confirmed that the thickness uniformity of the top and bottom of the TIN thin film deposited in Example 1 (SP-TiCl4) was superior in step conformality to the TIN thin film deposited in Comparative Example 1 (TiCl4). Here, the cross sections of the top and bottom can be illustrated in FIG. 6 below, where the top cross section was formed at a point 200 nm below the top, and the bottom cross section was formed at a point 100 nm above the bottom.

[0135] <Reference Example 1> The same process as in Example 1 was carried out, except that tert-butyl chloride was used instead of tert-butyl bromide as a growth inhibitor for thin film formation in Example 1, to form a TiN thin film as a self-limiting atomic layer. SIMS analysis was carried out to compare the impurity reduction characteristics, i.e., the reduction characteristics of process by-products, of the TiN thin film deposited according to Example 1, and the results are shown in Table 6 below.

[0136] [Table 6]

[0137] *Thickness: 10nm

[0138] As shown in Table 6, Example 1 using the bromide growth inhibitor for thin film formation according to the present invention had a higher Cl reduction rate and better impurity reduction properties than Reference Example 1 using the chloride growth inhibitor for thin film formation.

[0139] 5) Thin film crystallinity FIG. 8 below is an XRD analysis graph of Comparative Example 1 in which no growth inhibitor for thin film formation was added (Ref TiN), Example 4 in which the growth inhibitor for thin film formation was added at a rate of 0.1 / min (tert-BuI (0.1g / min)), and Example 4 in which the growth inhibitor for thin film formation was added at a rate of 0.1 / min (tert-BuI (0.1g / min)). As in Example 4, when the thin film precursor compound was first adsorbed and argon purged, and then the growth inhibitor for thin film formation of tert-BuI was adsorbed, it was confirmed that the crystal grains of the thin film became larger, that is, the crystallinity increased. Here, the size of the crystal grains can be confirmed by the peak at the (200) position of the TiN thin film (the larger and sharper the peak at the 200 position, the higher the crystallinity), and the increased crystallinity has the advantage of significantly improving the resistivity.

[0140] 6) Thin film density The density of the TiN thin film produced in Comparative Example 1 was 4.85 g / cm3. ... 3 However, the density of the TiN thin film produced in Example 4 using 0.01 g / min of tert-BuI was 5.00 g / cm 3 In Example 4, the density of the TiN thin film produced using 0.1 g / min of tert-BuI was 5.23 g / cm 3It was confirmed that the density of the thin film was significantly increased when the thin film precursor compound was first adsorbed, argon purged, and then the growth inhibitor for thin film formation, tert-BuI, was adsorbed as in Example 4. Therefore, the thin film according to the present invention has the advantage of improving the bending characteristics of an integrated structure having a high aspect ratio, such as the capacitance of a DRAM, and also having superior barrier metal characteristics.

[0141] Therefore, the present invention provides a thin film having a density of 4.95 g / cm 3 More than 5.00 g / cm 3 As a specific example, 4.95 to 5.50 g / cm 3 , and a preferred example is 5.0 to 5.3 g / cm 3 It is possible to provide a thin film in which

[0142] 7) Permeability of pellicle membrane The EUV transmittance of the pellicles (films) manufactured in Examples 7, 9 to 10 and Comparative Example 6 at a wavelength of 13.5 nm was measured using a transmittance analyzer, and the results are shown in Table 7 below. Here, the transmittance analyzer is not particularly limited as long as it is a commercially available transmittance analyzer. As an example, EUVO TM 40 is listed.

[0143] [Table 7]

[0144] As shown in Table 7, it was confirmed that the pellicle coated with the protective thin film of the present invention has the advantages of a protective thin film, while the transmittance is not significantly lower than that of the pellicle of Comparative Example 6, which is the reference, and is at a similar level.

[0145] 8) Hydrogen plasma resistance of pellicle membrane In order to confirm the resistance of the pellicles (membranes) coated with the protective thin films prepared in Examples 9 to 11 to H2 plasma, they were treated under the H2 plasma conditions in Table 8 below, and the results are shown in FIG. 10 below.

[0146] [Table 8]

[0147] As shown in Figure 10 below, a pellicle (CNT) not coated with a protective thin film was easily deteriorated during H2 plasma treatment, but a pellicle coated with a protective thin film according to the present invention was not deteriorated at all during H2 plasma treatment, confirming that the pellicle has excellent resistance to H2 plasma, i.e., chemical etching prevention effect. Figure 10 below shows SEM images of the surface of a pellicle film coated with a protective thin film prepared in Example 9 for TiN-CNT, Example 10 for HfO2-CNT, and Example 11 for SiO2-CNT after H2 plasma treatment.

[0148] 9) Degree of pellicle membrane defects The degree of defects of the pellicles (films) coated with the protective thin films manufactured in Examples 7 to 9 and Comparative Examples 6 to 8 was measured using a Raman spectroscopic analyzer (model name: NOST (Korea), manufacturer: FEX) with an incident laser wavelength of 531 nm, and the results are shown in FIG. 11 below. D / I G The lower the value, the lower the degree of defect.

[0149] Referring to FIG. 11 below, all of Examples 7 to 9 have a higher I than Comparative Examples 6 to 8, which correspond to the respective references. D / I G It was confirmed that the value of was significantly reduced and the degree of defects in the pellicle (membrane) was very low.

Claims

1. The following chemical formula 1 [Chemical formula 1] AnBmXo (wherein A is carbon, B is hydrogen or an alkyl having 1 to 3 carbon atoms, X is at least one of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), n is an integer of 1 to 15, o is an integer of 1 or more, and m is 0 to 2n+1), Growth inhibitor for forming a thin protective film for pellicles.

2. The pellicle is characterized in that it is made of CNT, fullerene, or a mixture thereof. The growth inhibitor for forming a pellicle protective thin film according to claim 1.

3. In the formula 1, o is an integer of 1 to 5. The growth inhibitor for forming a pellicle protective thin film according to claim 1.

4. The compound represented by formula 1 is a branched, cyclic or aromatic compound. The growth inhibitor for forming a pellicle protective thin film according to claim 1.

5. The compound represented by Formula 1 is used in an atomic layer deposition (ALD) process. The growth inhibitor for forming a pellicle protective thin film according to claim 1.

6. The compound represented by the formula 1 is liquid at room temperature (22° C.) and has a density of 0.8 to 1.5 g / cm 3 and characterized in that the vapor pressure (20°C) is 1 to 300 mmHg and the solubility in water (25°C) is 200 mg / L or less. The growth inhibitor for forming a pellicle protective thin film according to claim 1.

7. The following chemical formula 1 [Chemical formula 1] AnBmXo (wherein A is carbon, B is hydrogen or an alkyl having 1 to 3 carbon atoms, X is at least one of fluorine (F), chlorine (Cl), bromine (Br) and iodine (I), n is an integer of 1 to 15, o is an integer of 1 or more, and m is 0 to 2n+1) is introduced into an ALD chamber and adsorbed on the surface of the loaded pellicle, Method for forming a pellicle protective thin film.

8. i) vaporizing a growth inhibitor for forming the pellicle protective thin film and adsorbing it on the surface of the pellicle loaded in the ALD chamber; ii) initially purging the interior of the ALD chamber with a purge gas; iii) vaporizing a precursor compound of the pellicle protective film and adsorbing it on the loaded pellicle surface in the ALD chamber; iv) second purging the interior of the ALD chamber with a purge gas; v) supplying a reactive gas into the ALD chamber; and vi) tertiary purging of the interior of the ALD chamber with a purge gas, The method for forming a pellicle protective thin film according to claim 7.

9. i) vaporizing and adsorbing a precursor compound of a pellicle protective film onto a loaded pellicle surface in an ALD chamber; ii) initially purging the interior of the ALD chamber with a purge gas; iii) vaporizing a growth inhibitor for forming the pellicle protective thin film and adsorbing it on the surface of the loaded pellicle in the ALD chamber; iv) second purging the interior of the ALD chamber with a purge gas; v) supplying a reactive gas into the ALD chamber; and vi) tertiary purging of the interior of the ALD chamber with a purge gas, The method for forming a pellicle protective thin film according to claim 7.

10. The growth inhibitor for forming the pellicle protective thin film and the precursor compound of the pellicle protective thin film are transferred into the ALD chamber by a VFC method, a DLI method or an LDS method. The method for forming a pellicle protective thin film according to claim 8 or 9.

11. The ratio of the amount (mg / cycle) of the growth inhibitor for forming the pellicle protective thin film and the precursor compound of the pellicle protective thin film introduced into the ALD chamber is 1:1.5 to 1:

20. The method for forming a pellicle protective thin film according to claim 8 or 9.

12. The method for forming a pellicle protective thin film is characterized in that the reduction rate of the thin film growth rate per cycle (Å / Cycle) calculated by the following Equation 1 is -5% or less: The method for forming a pellicle protective thin film according to claim 8 or 9. [Formula 1] Decrease rate (%) of thin film growth rate per cycle = [(thin film growth rate per cycle when a growth inhibitor for forming a pellicle protective thin film is used - thin film growth rate per cycle when a growth inhibitor for forming a pellicle protective thin film is not used) / thin film growth rate per cycle when a growth inhibitor for forming a pellicle protective thin film is not used] x 100

13. The method for forming a pellicle protective thin film is characterized in that the strength (c / s) of residual halogen in the thin film formed after 200 cycles is 10,000 or less as measured by SIMS. The method for forming a pellicle protective thin film according to claim 8 or 9.

14. The reactive gas is a reducing agent, a nitriding agent or an oxidizing agent. The method for forming a pellicle protective thin film according to claim 8 or 9.

15. A mask and a pellicle covering a surface of the mask, The pellicle is made of CNTs, fullerenes, or a mixture thereof; The surface of the pellicle is coated with a protective thin film; The protective thin film is a TiN protective thin film, a TiO 2 Protective film, NbN protective film, or HfO 2 It is a protective thin film, The protective thin film has a halogen content of 1 ppm to 9,000 ppm.

Citation Information

Patent Citations

  • Method for forming EUVL pellicle

    JP2021107916A

  • KR2006-0037241

  • Pellicle for photomask, reticle including the same, and exposure apparatus for lithography

    US20180259844A1

  • Pellicle film, pellicle frame, pellicle, method for producing same, original plate for light exposure, light exposure apparatus and method for manufacturing semiconductor device

    WO2018008594A1